The Role of Legal and Social Policies in Attaining Sustainable Urban Development in India - Samal, Manohar (European Journal of Sustainable Development, 2019)
This paper intends to explicate the present framework of legal and social policies in India, which govern urban development. The research is directed towards contemplating the progress of sustainable urbanism in India in achieving the goals of the 2030 Agenda for Sustainable Development. Overcrowding, rise in the number of informal settlers and unplanned development are the most prominent multi- faceted issues that India faces in the present day. A comprehensive analysis of urban development policies, environmental legislation, property laws and information laws have been discussed in order to exhibit the lacunae in the legal system which has slowed down the process of sustainable urban development in India. It is not only the policies, but also an array of problems that, have affected urban development in metropolitan cities, semi- urban regions and transitioning rural areas rendering them to be unsustainable. Therefore, this paper envisages and suggests solutions in tackling problems in legal and social policies that would make sustainable urbanism conducive and successful in India. An attempt has also been made to display how completely sustainable urban spaces would look in India. Analytical, Comparative and Doctrinal methods of research have been utilized to conduct the research. Keywords: Development, Local Self Government, Policies, Sustainable, India